Improving the cold flow properties of marine diesel fuel using centrifugation - Yakovlev, Nikolay S.; Agaev, Vyacheslav G.; Zemlyansky, Evgeniy O. (Revista de la Universidad del Zulia, 2020)
The possibility of improving the low-temperature properties of marine diesel fuel of the Antipinsky Refinery by dewaxing was studied. Paraffin was isolated from the fuel in a centrifuge in the presence of a depressant additive. The depressant additive is selected from a series of synthesized additives for depressant effectiveness. The influence of the centrifuge rotor speed, the additive content and the initial cooling temperature of the sample on the dewaxing parameters of the fuel was studied. The possibility of isolating the additive from the obtained paraffin concentrates is shown. The dewaxing products obtained under optimal conditions were studied. A paraffin concentrate product containing 40.03% solid paraffins was isolated from fuel. Paraffin was isolated from paraffin concentrate by dewaxing with a selective solvent. The cloud point and freezing point of paraffin were 30 and 29 ° C, respectively. When converted to the original fuel, the amount of released paraffins was 7.3% of the 21% by weight contained in the original fuel. The fuel obtained at optimal parameters for low temperature properties corresponds to grade D of diesel fuel according to EN 590: 2009.